CONTENT AND LANGUAGE INTEGRATED LEARNING (CLIL) IN THE CLASSROOM: INDONESIAN TEACHERS’ EXPERIENCES AND CHALLENGES - Mustafa, Haris; Suryani, Suryani; Elyza, Ferlya (Jurnal Dedikasi Pendidikan, 2025)
This study investigated Indonesian teachers' perceptions of Content and Language Integrated Learning (CLIL) implementation at Fatih Bilingual School Banda Aceh. Guided by Vygotsky's zone of proximal development theory, the research employed a mixed-methods approach, combining case study and interview techniques. Data were collected from eight teachers who taught subjects in English, with two teachers selected for in-depth interviews. Findings revealed positive perceptions of CLIL among teachers, who reported improvements in both students' language and content knowledge. Despite limited prior knowledge of CLIL, teachers expressed enthusiasm for its potential to enhance learning. However, challenges emerged, particularly in working with English beginner students and managing the demands of teaching both content and language simultaneously. The study's implications for CLIL implementation in Indonesian schools include the need for ongoing professional development and support for teachers, as well as the importance of carefully considering the language proficiency levels of students. Future research could explore the long-term effects of CLIL on student outcomes and investigate its effectiveness in different educational contexts